Prognostic factors in stage IV oropharyngeal squamous cell carcinoma: the “punto” experience - Piccinini, Alessia; Alicandri-Ciufelli, Matteo; Ghidini, Angelo; Vincenti, Vincenzo; Ferri, teore; Presutti, Livio (Acta Biomedica Atenei Parmensis, 2016)
Purpose:  Squamous Cell Carcinoma (SCC) of Oropharynx is often diagnosed in advanced stages. Treatment options have improved during recent years, however the choice of most appropriate treatment is still controversial. Prognostic factors can help to optimize the care. This study investigate the role of 9 potential prognostic factors, including HPV status, in Oropharyngeal SCC.Materials and Methods: Nine prognostic factors were investigated in a retrospective chart of 98 patients treated for stage IV SCC of Oropharynx from january 2006 to january 2012, including  age (60), gender, tumor subsite , histological grading, T stage, N stage, AJCC stage, BMI pre-treatment and HPV status. Moreover treatment modalities were compared  and the data regarding the treatment factors, like radiotherapy technique and kind of chemotherapy  were collected and compared.Primary endpoint was the impact of the prognostic factors on OS, DFS and DSS.Seconrdary endopoint were the impact of these factors on QOL and Toxicity.Results: On univariate analisys significant improved OS was associated with age < 60 (p= 0,004), grading G3 (p=0.003), BMI > 25 (p= 0.03), radiotherapy with IMRT/SIB IMRT  technique (p=0,01) and AJCC stage IVa (p=0,01).No prognostic factor was associated to DFS improvement.Instead a significant improved DSS was associated with age 25.